PENERAPAN METODE INQUIRI DALAM MENINGKATKAN KETERAMPILAN MEMPREDIKSI DAN PEMAHAMAN KONSEP BELAJAR SISWA PADA POKOK BAHASAN PERUBAHAN WUJUD BENDA KELAS V SD ISLAM NW CEKING TAHUN PELAJARAN 2021-2022 - Suryawati, Ely (Jurnal Ilmiah Mandala Education (JIME), 2022)
In carrying out learning activities the teacher tries to use the inquiry learning method to make students more active, creative and critical and can solve problems so as to improve student achievement. This study aims to determine whether the application of the inquiry learning method in improving the skills of predicting and understanding student learning concepts on the subject matter of changing the shape of objects in class V Islamic Elementary School NW Ceking. The type of research used is classroom action research (CAR). The instruments used are tests, observations and documentation. This research was conducted in two cycles with two evaluations. Based on the results of the evaluation and observation in each cycle, the learning outcomes obtained can be seen in the evaluation results, namely the first cycle with an average value of 60.43 with classical completeness of 52.17%, and in the second cycle there is an average value of 74.56 with a classical completeness percentage of 91.30%. This shows that complete learning has been achieved in accordance with the existing curriculum. Thus the application of the inquiry method in improving predictive skills and understanding of student learning concepts on the subject matter of changing the shape of objects in class V Islamic Elementary School NW Ceking